Abstraction and its relationship visual attraction designs in women's modern fabrics: حيدر هاشم محمود الحسيني (Al-Academy, 2016)
The research problem identified to impose question followingDoes the abstract style role in the backs of visual attraction in modern textile designs?The research aims to reveal the role of the external design in modern women's textile designs printed, design and develop foundations for practical purposes to achieve visual attraction through abstract style used in the design of modern women's fabricsIn regard to the second quarter, which contained the theoretical framework and previous studies, it was included in the board three sections, the first section included the concept of abstraction, while the second section included in place of attraction and infrastructure design, In regard to the third topic was concerned with the concept of modernity.The third chapter dealt with the search procedures, as follow researcher descriptive survey method (content analysis).It then took the fourth quarter results and conclusions Among the most important are:1-Most designs have focused on non-formal vocabulary familiar style design using geometric abstract and abstract2-Adoption of the formal organization of the distribution of the design vocabulary clearly and effectively, using linear regulation and synthesis and irregular (random) as the most important systems used in the distribution of work within the vocabulary designBased on Helms of sequential procedures for research and development researcher most important cornerstones design that achieved through visual attraction abstract style used in the design of the cloth, as follows:1-Reliance on abstract art 'as a method of forming an unfamiliar configurations according to a new vision of contemporary creativity in the field of technical configuration, surpassing copying and imitation to what is beyond, stems from the same designer in a new context is far from the rules and artistic traditions